On the Two Essential Concepts for SFT: Synergetic Buoyancy-weight Ratio and Slack-taut Map. (2016) - Hong, Youshi; Ge, Fei; Lu, Wei
Abstract: In the submerged floating tunnel (SFT) design and future construction, buoyancy-weight ratio (BWR) and slack-taut performance (STP) are two intrinsic issues with respect to the SFT dynamic response and stability under the structural and external loadings. BWR is defined as the ratio of tunnel buoyancy to the whole tunnel weight. Our experiments and numerical simulations indicate that BWR dominates the dynamic response of SFT and is the most important parameter to be considered in SFT design. For this, we re-state the essential concept of "Synergetic range of BWR". This is regarded as, for an SFT structure with related environmental conditions, a suitable range of BWR value exists, which will lead to less dynamic response and more stable for the SFT. STP is the tether slacking and the related snap force under sea wave conditions. Our simulation results show that SFT tether may go slack and induce snap force at a large wave height at a certain combination of BWR and inclined morning angle (IMA) of the tether. As the second essential concept for SFT, a Slack-Taut Map of SFT is constructed, which describes the occurrences of slack and snap force (under a certain wave condition) as a function of BWR and IMA.